Ibn Mozaffar AI-Yemeni and His BooK " Al-Kawākib Al-Nayyirah" (Study and Veriflcation of Revocability and Difference Parts) - Al-Awadi, Ramzi Abbas Ahmed Muhammad (Journal of Islamic Sciences, 2023)
This research aims to introduce the scholar Yahya bin Ahmed bin Ali bin al-Muzaffar (died in A. H. 875) and shed light on his scholarly knowledge, books, methodology, and sources in his book, "Al-Kawākib Al-Nayyirah Kāshif Maeani Al-Tadhkirah Al-Fākhirah Fi Fiqh Al-'Itrah Al-Táhirah". The researcher applies the inductive, historical, and descriptive approach, and verifies the author's book title. The book contains rich Islamic jurisprudential views and insightful jokes, which are indispensable for every scholar and knowledge seeker.
Keywords: Yahya Ahmed Ali Al-Muzaffar; Methodology; Al-Kawākib Al-Nayyirah Kāshif Maeani Al-Tadhkirah